Pediatric spinal cord diffuse midline glioma, H3 K27-altered with intracranial and spinal leptomeningeal spread: A case report. Issue 5 (October 2022) - Serrallach, Bettina L; Tran, Brandon H; Bauer, David F; Mohila, Carrie A; Adesina, Adekunle M; McGovern, Susan L; Lindsay, Holly B; Huisman, Thierry AGM
Primary spinal cord high-grade gliomas, including those histologically identified as glioblastoma (GBM), are a rare entity in the pediatric population but should be considered in the differential diagnosis of intramedullary lesions. Pediatric spinal cord high-grade gliomas have an aggressive course with poor prognosis. The aim of this case report is to present a 15-year-old female adolescent with histopathologically confirmed spinal cord GBM with H3F3A K27 M mutation consistent with a diffuse midline glioma (DMG), H3 K27-altered, CNS WHO grade 4 with leptomeningeal seeding on initial presentation. As imaging features of H3 K27-altered DMGs are non-specific and may mimic more frequently encountered neoplastic diseases as well as demyelinating disorders, severe neurological deficits at presentation with short duration, rapid progression, and early leptomeningeal seeding should however raise the suspicion for a pediatric-type diffuse high-grade glioma like DMG, H3 K27-altered.